Outcomes of Venous Malformation Sclerotherapy: A Review of Study Methodology and Long-Term Results - Ali, Sumera; Mitchell, Sally E. (Seminars in Interventional Radiology, 2017)
It is very important that patients seeking sclerotherapy for the treatment of venous malformations are aware of the expected course of the therapy. They should be thoroughly counseled about the complications, the need for multiple sessions of therapy, and also about the expected clinical outcome. The aim of this review is to discuss the long-term outcomes of sclerotherapy for the treatment of venous malformation. Many studies have discussed their individual center's experiences and short-midterm results, but there is a relative paucity of data on long-term outcomes. We have reviewed the literature and also shared our experience of a large cohort of patients (n = 116) with a relatively longer follow-up period of more than 1 year. Venous malformations are very complex lesions and their treatment is quite variable depending on its extent and complexity. As a result, outcome studies vary considerably in the choice of sclerosant, study methodology, outcome assessment (clinical vs. imaging), and grading scales. This review also highlights this extreme heterogeneity in the literature of the sclerotherapy outcome and summarizes a few national and international studies for comparison.
Keywords: venous malformation; sclerotherapy; interventional radiology